Biochemical basis of resistance to pod borer (Helicoverpa armigera) in Australian wild relatives of pigeonpea. Issue 4 (20th May 2021) - Vanambathina, Prameela; Rachaputi, Rao C. N.; Sultanbawa, Yasmina; Phan, Anh Dao Thi; Henry, Robert J.; Brier, Hugh
Abstract: The domestication of pigeonpea has severely impacted the intrinsic host‐plant resistance (HPR) to pest and diseases, particularly pod borer ( Helicoverpa armigera hubner). This study with 41 Australian wild Cajanus genotypes and interspecific hybrids demonstrated a high level of resistance to H. armigera in the accessions of Cajanus acutifolius, C. latisepalus, C. lanceolatus, C. pubescens, and C. reticulatus var. reticulatus . Significant variation in herbivory development and mortality ( P < 0.001) was observed in the wild accessions and their hybrids in response to feeding on leaves. A strong positive relationship ( R 2 = 0.69, P < 0.001) between total phenolic compounds (TPC) and the HPR was observed. Australian wild genotypes demonstrated the role of TPC and the absence of certain flavonoids such as rutin and quercetin in resistant genotypes. The detached leaf bioassay technique separated the wild and domesticated accessions into wild resistant, with herbivory weight difference (HWD) (Day 7–Day 1) ranging between −27 ‐ 104 mg, wild susceptible, with HWD ranging between 124 ‐ 207 mg and domesticated susceptible, with HWD ranging from 208 ‐ 300 mg. Similarly, based on TPC, accessions were also categorised into wild high TPC, with TPC ranging between 32.3 ‐ 42.5 GAE mg/g DW, and wild low TPC had only 17.2–24.8 GAE mg/g DW. Low TPC concentrations were found in domesticated pigeonpea, with 10.7–17.6 GAE mg/g DW. The presence of very high concentrations of the flavone isoorientin, an important antioxidant implicated in the intracellular defence mechanism of cancer therapy, was identified for the first time in wild species of pigeonpea.